A Self‐Powered Triboelectric Nanosensor for Mercury Ion Detection. Issue 19 (8th April 2013) - Lin, Zong‐Hong; Zhu, Guang; Zhou, Yu Sheng; Yang, Ya; Bai, Peng; Chen, Jun; Wang, Zhong Lin
Abstract : Moving to mercury : The first triboelectric effect‐based sensor for the detection of Hg 2+ ions by using Au nanoparticles (see picture; red) as electrical performance enhancer and recognition element has been successfully demonstrated. This self‐powered and stand‐alone triboelectric nanosensor has the advantages of simplicity, low cost, high selectivity, and sensitivity.